JAMINAN KEPASTIAN HUKUM TERHADAP ANAK YANG LAHIR DI LUARNIKAH DAN TINJAUAN MENURUT HUKUM ADAT DAYAK KENYAH - Ekaristi Ekaristi (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Recording of marriage plays a decisive role in a marriage because marriage registration is a requirement of whether or not a marriage is recognized by the state. The guarantee of legal certainty for children born out of wedlock according to DayakKenyak customary law is to know the guarantee of legal certainty to children born out of wedlock. The purpose of this study is to find out how the legal protection of children born outside marriage according to Law no. I of 1974 and the Civil Code and the ceremonial and symbolic arrangements used in the indigenous DayakKenyah marriage. The research method used is normative law research method by analyzing from books and discussions with Indigenous apparatus in MahakBaru Village. By formal law as set forth in Law No.1 of 1974 article 43 verse 1 that a child born outside marriage has only a civil relationship with his mother and his mother's family. The results showed that children's right to obtain legal certainty Dayak Kenyah Indigenous born out of marriage there is no difference of rights with children born legally in Indigenous DayakKenyah result of discussion with customs apparatus and books about Indigenous Dayak Kenyah law.